A Review on Modeling Techniques of Cementitious Materials under Different Length Scales: Development and Future Prospects. Issue 7 (22nd May 2019) - Wang, Xing Quan; Chow, Cheuk Lun; Lau, Denvid
Abstract: Modeling can provide guidelines for improving the mechanical properties, durability, and sustainability of concrete, which is the most important and widely used construction material in today's world. This review aims to summarize the modeling of cementitious materials from the historical perspective. The development of macroscopic constitutive models and computational methods for concrete at macro‐scale is presented first. However, the existing macroscopic models are insufficient to explain fundamentally the deformation and failure of concrete. In order to understand the atomic interaction that governs the material behavior, molecular dynamics (MD) simulations should be adopted in order to understand the fundamental deformation mechanisms of cement, fiber‐reinforced polymers (FRP), and related systems. Coupled with the development of nano‐scale modeling, multi‐scale modeling is introduced in order to build linkage between nano‐scale and macro‐scale models. This paper provides a clear understanding of the limitations and potentials of different modeling methods, as well as the development trend of cementitious materials. The future prospect of the nano‐engineering approach is illustrated so as to inspire the improvement of construction materials. Additionally, the key challenges associated with cementitious material modeling are discussed. Abstract : Because of the wide applications of concrete, the modeling of concrete is important in academia. In this paper, the development of cementitious materials modeling is summarized with an emphasis on nano‐engineering approaches. This paper provides a clear understanding of limitations and potentials of different modeling methods. Also, the key challenges and future prospects of modeling are presented.